Penerapan Metode Resitasi pada Mata Pelajaran Fiqih untuk Meningkatkan Motivasi Belajar Siswa - Zulmi Zulmi; Rosmiati Rosmiati; Ratika Nengsi (Education and Learning Journal, 2023)
This study discusses the application of the Recitation Method in the Subject of Fiqh to Increase the Learning Motivation of Grade VII A Students at MTSN 1 Central Buton, Central Buton Regency. In this thesis the main points of discussion are: 1) How to apply the Recitation Method in Fiqh Subjects to Increase Student Motivation in Class VII A MTsN 1 Central Buton, Central Buton Regency 2) Can the application of the Recitation Method increase Student Learning Motivation in Fiqh Class Students VII A MTSN 1 Central Buton, Central Buton Regency. The purpose of this study was to increase students' learning motivation in the subject of Fiqh class VII A at MTsN 1 Buton Tengah, Central Buton Regency by using the Recitation method. Recitation is a learning method in which the teacher gives certain tasks so that students carry out learning activities, then they must be held accountable. The teacher needs to know and be aware of his students, namely learning that is well mastered by students, and one of the ways to do this is that the assignments given are not only done in class but need to be done at home or anywhere and the results must be accounted for. This research is a Classroom Action Research (CAR) conducted in two cycles. Silkus 1 consists of 3 meetings while cycle 2 consists of 2 meetings where one cycle consists of 4 stages, namely planning, action, observation, and reflection. The subject of this study was class VII A at MTsN 1 Buton Tengah with a total of 20 students consisting of 8 male students and 12 female students. The results of this study indicate that the learning motivation of students in class VII A increases after using the Recitation method in Fiqh subjects. In cycle, I, students' learning motivation was 70.77% which means that in this first cycle, the motivation of students in class VII A is not optimal and is still moderate. And in cycle II, students' learning motivation increased to 93.46%, which means that students' learning motivation reached a maximum score or high score.